Stopping the Anthropological Machine: Agamben with Heidegger and Merleau-Ponty - KELLY OLIVER (PhaenEx: Journal of Existential and Phenomenological Theory and Culture, 2007)
Agamben maintains that Heidegger continues the work of the anthropological machine by defining Dasein as uniquely open to the closedness of the animal. Yet, Agamben’s own thinking does not so much open up the concept of animal as it attempts to save humanity from the anthropological machine that always produces the animal as the constitutive outside within the human itself. Agamben’s return to religious metaphors at best displaces the binary man-animal with the binary religion-science, and at worst returns us to a discourse at least as violent as the one from which he is trying to escape. Merleau-Ponty’s reanimation of science provides an alternative.